Soft Sediment Deformation Structures in the Andaman Flysch Group, Andaman Basin: Evidence for Palaeogene Seismic Activity in the Island Arc - Sandip K. Roy; Santanu Banerjee (Ikatan Ahli Geologi Indonesia, 2016)
The Andaman Flysch Group is represented by four sedimentary facies: thick sandstone, thin sandstone, heterolith and shale. They were observed in seven outcrops in the Andaman Islands. Soft sediment deformation features like slumps structure/folds, convolute bedding or lamination, load and flame structures, pseudo nodules/ball and pillow structures and dish and pillar structures have been observed with regularity in these facies and independent of facies specifics. The slumps structure/folds, convolute bedding or lamination encased by undeformed beds, sand volcanoes and some load casts/pseudo-nodules shows evidence of being triggered by earthquakes in this convergent margin basin.